Crystal structure analysis of phycocyanin from chromatically adapted Phormidium rubidum A09DM. Issue 81 (16th August 2016) - Gupta, Gagan Deep; Sonani, Ravi R.; Sharma, Mahima; Patel, Krishna; Rastogi, Rajesh P.; Madamwar, Datta; Kumar, Vinay
Abstract : Structural and sequence analyses of Phormidium phycocyanin revealed three co-evolving residues that determine the conformation of a phycocyanobilin chromophore believed to play role in alternate pathways for intra and inter-rod energy transfer. Abstract : Phycobilisome (PBS), a light harvesting complex of phycobili proteins found in cyanobacteria and red algae, funnels photo-energy to chlorophyll through the network of covalently attached light absorbing chromophores. Phycocyanin, a component protein of PBS, was over-expressed using monochromatic red light in place of white light by chromatically adapted Phormidium rubidum A09DM. The phycocyanin protein, having α- and β-subunits, was isolated and purified in active and chromophorylated form as adjudged by PAGE, MALDI-TOF and spectroscopic analysis. The crystals, obtained using PEG-3350 as a precipitant, belong to the P 63 space group with unit cell parameters a = b = 102.40 Å, c = 109.05 Å. The structure has been refined to a crystallographic R factor of 20.7% ( R free, 25.8%) using X-ray diffraction data extending up to 2.7 Å resolution. The asymmetric unit consists of two αβ monomers. The functional unit [(αβ)3 ]2 hexamer is generated by the application of crystal symmetry. The overall tertiary structure of α- and β-subunits and hexameric quaternary fold of the Phormidium protein resemble the other reported PC structures, except for the conformation of chromophore attached to βCys-153. The structure and sequence analyses reveal that residues αPhe-28, αGln-33 and αAsp-145 (of α-subunit) are co-evolving and play a key role in determining the conformation of this chromophore. These phycocyanins cluster together in an evolutionary tree and are expected to have evolved later.